Nitrogen/sulfur dual-doping of reduced graphene oxide harvesting hollow ZnSnS3 nano-microcubes with superior sodium storage. (March 2019) - Liu, Xiaojing; Hao, Youchen; Shu, Jie; Sari, Hirbod Maleki Kheimeh; Lin, Liangxu; Kou, Huari; Li, Jianwei; Liu, Wen; Yan, Bo; Li, Dejun; Zhang, Jiujun; Li, Xifei
Abstract: Bimetallic sulfides have exhibited promising applications in advanced sodium-ion batteries (SIBs) due to their relatively high electronic conductivity and electrochemical activity. In this study, for the first time, the N/S dual-doped reduced graphene oxide (rGO) encapsulating hollow ZnSnS3 nano-microcubes (N/S-rGO@ZnSnS3 ) is designed to improve the sluggish reaction kinetics, poor cycling stability and unsatisfactory rate capability of metal sulfides. To examine this design, the cycling stability and rate capability of the desired anode material is studied in detail. It is found that N/S-rGO@ZnSnS3 hybrid delivers a high discharge capacity of 501.7 mAh g −1 after 100 cycles at 0.1 A g −1, and a reversible capacity of 290.7 mAh g −1 after 500 cycles at 1.0 A g −1 with a capacity fading of 0.06% per cycle. The cycling stability as well as rate capability of N/S-rGO@ZnSnS3 are superior to those of the pristine hollow ZnSnS3 cubes/un-doped rGO composite. It is convinced that the electrode performance is strongly rooted in its structural conformation. Furthermore, the structural evolutions of ZnSnS3 reactions with sodium are revealed by in situ X-ray diffraction combined with ex situ X-ray photoelectron spectroscopy, which provides a valuable revelation for the understanding of reaction mechanism toward bimetallic sulfides and beyond. Graphical abstract: Hollow ZnSnS3 nano-microcubes encapsulated into N/S dual-doped rGO presents superior cycling stability and rate capability for Na storage due to the simultaneous improvements in structural stability, electronic conductivity, electrochemical activity, and reaction kinetics. fx1 Highlights: N/S dual-doped rGO encapsulating hollow ZnSnS3 cubes are successfully fabricated. The structural advantages and reaction kinetics of the resultant electrodes is revealed. The desired electrode delivers superior cycling stability and rate capacity for Na-storage. The structural evolutions of ZnSnS3 reaction with sodium are systematically studied.